Precision Nutrition and Reliability of Continuous Glucose Monitors: Insights From the PREDICT Study. (7th June 2021) - Merino, Jordi; Berry, Sarah; Ganesh, Sajaysurya; Capdevila, Joan; Drew, David; Bakker, Elco; Wolf, Jonathan; Franks, Paul; Chan, Andrew; Spector, Tim; Ordovas, Jose; Valdes, Ana
Abstract: Objectives: The use of continuous glucose monitors (CGM) provides a more in-depth characterization of glycemic variation in response to environmental stimuli, but concerns about CGM reliability for categorizing glycemic responses to foods and meals exist. We sought to evaluate the concordance and reliability of two simultaneously worn CGM devices on postprandial glycemic responses. Methods: We examined the correlation and coefficient of variation of the 2h glucose incremental area under the curve (iAUC) for 21, 527 standardized and ad libitum meals consumed by 368 healthy participants from the PREDICT-1 Study. Included participants were simultaneously monitored with either two Abbott Freestyle Libre Pro devices (n = 339, same device group) or the combination of Abbott Freestyle Libre Pro and Dexcom G6 devices (n = 29, inter device group). Within-subject 2 h iAUC glucose meal rankings for paired CGM devices were assessed using the Kendal-tau measure for ranking concordance. Results: The correlation coefficient of the 2 h glucose iAUC for paired CGM devices was 0.97 (95% CI, 0.96 to 0.97) for same device comparisons and 0.78 (0.76 to 0.80) for inter device comparisons. The coefficient of variation of the 2 h glucose iAUC for standardized meals was 5.1% (interquartile range, 2.2 to 10.1) for same device comparisons and 15.1% (5.9 to 31.2) for inter device comparisons. Similar results were observed for ad libitum meals with same and inter device coefficients of variation of 8.9% (3.3 to 21.3) and 24.2% (10.2 to 53.1%), respectively. Meal rankings for the 2 h glucose iAUC were concordant between paired CGM devices, with a mean Kendall rank correlation coefficient of 0.86 (sd = 0.07) for same device comparisons and 0.63 (sd = 0.011) for inter device comparisons. Conclusions: These data provide evidence for repeatability and concordance for ranking of glycemic responses, and suggest that factors other than CGM sensors mostly drive within-subject meal categorization. Our findings are critical for identifying sources of variability in glycemic responses for the eventual implementation of precision nutrition. Funding Sources: Zoe Global, UK Government Department of Health and Social Care, Wellcome Trust. National Institutes of Health.